THE CURRICULUM DEVELOPMENT OF ABHIDHAMMAPITAKA FOR LIFELONG LEARNING - Buasiri, Amnaj; PhraRattanamuni; Koomkrong, Viroj (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aimed to 1) study the current status, problems, causes and obstacles to Abhidhamma education of Buddhists in Thailand, 2) study the components of the development of an Abhidhamma curriculum structure for lifelong learning, and 3) develop and evaluate the curriculum structure for lifelong learning. This qualitative research used document study, participatory discussion, interviews and environmental analysis. There were 15 informants, 8 expert workshops, and 5 experts evaluated the curriculum suitability. Data were analyzed by content analysis. The results of the research found that 1) the problems, causes and obstacles to Abhidhamma education management as summarized from the environmental analysis (1) unclearly promoted as a policy of the Sangha, there were no agencies of the Supreme Sangha Council and government agencies related to Buddhism to provide care and support. (2) The administration of the school and academic administration in the school were not yet standardized. (3) The learning management did not divide the study sequence according to the age range of the students. The learning was mixed for each age group. (4) The learning media, supporting activities, and measurement and evaluation were not diverse. (5) The curriculum structure had not been developed according to the standard. 2) Components of the development of the Abhidhamma curriculum structure for lifelong learning consisted of 7 parts: (1) principles, (2) goals, (3) desired characteristics, (4) education level, (5) academic management consisting of learning management content, learning time management, learning media, learning enhancement activities, measurement and evaluation of learning outcomes. (6) teachers, (7) curriculum management and 3) the development of the Abhidhamma curriculum structure for lifelong learning as following: (1) principles of Abhidhamma study, (2) goals of Abhidhamma study, (3) desired characteristics of learners, (4) levels of Abhidhamma study, consisting of 9 parts in 3 age groups corresponding to early childhood to the elderly. (5) Abhidhamma academic administration useed the standard curriculum from Abhidhammajotika College as a model, classified into 9 parts, starting from Chula Abhidhammaka to Maha Abhidhamma, bachelor’s, master’s and doctoral degrees. Active learning management was used by providing media, supporting equipment, learning enhancement activities, and a variety of learning assessment and evaluation, using modern digital technology appropriate for the age to support. (6) Abhidhamma teachers were supported to develop knowledge, skills and experience continuously as a professional, (7) Curriculum management has been developed to have a system that met international standards and the results of the evaluation of the Abhidhamma curriculum structure for lifelong learning had been evaluated for suitability in terms of components, application, feasibility and overall beneficial use at a high level.